Urinary metabolites of type 2 diabetes rats fed with palm oil-enriched high fat diet. Issue 9 (September 2021) - Sim, Xuan-Yi; Ibrahim, Baharudin; Gam, Lay-Harn
Abstract: High fat diet (HFD) is one of the risk factors of obesity and diabetes. Recommended diet regimen for diabetes is difficult to abide by especially for HFD as it adds flavour to the taste buds. In this study, palm oil-enriched HFD and normal diet were fed to nicotinamide-induced type 2 diabetes rats, respectively for six weeks. Additionally, metformin, a common drug used to treat diabetes was given to rats under treatment groups. We evaluated the change of urinary metabolites of diabetes rats fed with palm oil-enriched HFD, and also after metformin treatment. Rats were divided into six-groups with different feeding diets, disease condition and with or without metformin treatment. Rats' urine were collected at the end of six weeks feeding program and subjected to 1H-NMR and multivariate data analysis to evaluate their metabolite profiles. At the early phase of diabetes, metabolites changes in diabetic rats were associated with the disease itself. Our data showed that continuous consumption of HFD altered various metabolic pathways of diabetic rats and caused detrimental effects to the rats. On the other hand, metformin treatment combined with normal diet lessened the physiological impacts caused by diabetes condition. Abstract : Metabolites, NMR, Diabetes, High Fat Diet, Metformin.